Tuberculosis and homelessness in Montreal: a retrospective cohort study - Tan de Bibiana Jason; Rossi Carmine; Rivest Paul; Zwerling Alice; Thibert Louise; McIntosh Fiona; Behr Marcel A; Menzies Dick; Schwartzman Kevin (BMC, 2011)
Abstract Background Montreal is Canada's second-largest city, where mean annual tuberculosis (TB) incidence from 1996 to 2007 was 8.9/100,000. The objectives of this study were to describe the epidemiology of TB among homeless persons in Montreal and assess patterns of transmission and sharing of key locations. Methods We reviewed demographic, clinical, and microbiologic data for all active TB cases reported in Montreal from 1996 to 2007 and identified persons who were homeless in the year prior to TB diagnosis. We genotyped all available Mycobacterium tuberculosis isolates by IS6110 restriction fragment length polymorphism (IS6110-RFLP) and spoligotyping, and used a geographic information system to identify potential locations for transmission between persons with matching isolates. Results There were 20 cases of TB in homeless persons, out of 1823 total reported from 1996-2007. 17/20 were Canadian-born, including 5 Aboriginals. Homeless persons were more likely than non-homeless persons to have pulmonary TB (20/20), smear-positive disease (17/20, odds ratio (OR) = 5.7, 95% confidence interval (CI): 1.7-20), HIV co-infection (12/20, OR = 14, 95%CI: 4.8-40), and a history of substance use. The median duration from symptom onset to diagnosis was 61 days for homeless persons vs. 28 days for non-homeless persons (P = 0.022). Eleven homeless persons with TB belonged to genotype-defined clusters (OR = 5.4, 95%CI: 2.2-13), and ten potential locations for transmission were identified, including health care facilities, homeless shelters/drop-in centres, and an Aboriginal community centre. Conclusions TB cases among homeless persons in Montreal raise concerns about delayed diagnosis and ongoing local transmission.